Hubungan Perilaku Sleep Hygiene dengan Kejadian Insomnia pada Lansia - Hasanah, Ananda Maqfirotul; Dewi, Sofia Rhosma; Elmaghfuroh, Dian Ratna (Indonesian Journal Publisher, 2025)
Background: Aging in the elderly is accompanied by various physiological changes, including sleep disturbances such as insomnia, which can reduce quality of life. One non-pharmacological intervention that can be used to reduce insomnia is the application of sleep hygiene behavior. Purpose: To determine the relationship between sleep hygiene behavior and the incidence of insomnia in the elderly. Methods: This study employed a quantitative correlational design with a cross-sectional approach, conducted in May 2025. A sample of 67 elderly individuals was selected using purposive sampling from a total population of 80. Data were collected using the Sleep Hygiene Index (SHI) and a modified version of the Sleep Condition Indicator (SCI), both of which were tested for validity and reliability. Data were analyzed using the Spearman Rank test with the assistance of SPSS at a significance level of α < 0.05. Results: Most respondents had moderate sleep hygiene behavior (41.8%), and more than half experienced insomnia (52.2%). Statistical tests showed a significant and strong relationship between sleep hygiene behavior and the incidence of insomnia, with a p-value of 0.000 and a correlation coefficient r = 0.643. The positive correlation indicates that the worse the sleep hygiene behavior, the higher the risk of insomnia. Conclusion: These findings suggest that sleep hygiene is an effective non-pharmacological strategy in preventing or reducing the incidence of insomnia. The results of this study are expected to serve as a reference and guideline for Tresna Werdha in designing programs aimed at improving sleep quality among the elderly.